Aktualisasi Nilai Al-Qur’an Bagi Generasi Muda yang Berkulitas dan Berwawasan - Prapti Octavia Ningsih; Eko Parnandes; Tantri Wulandari; Nor Ainun (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
This community service aims to actualize the values ​​of the Qur'an through the Musabaqoh Tilawatil Qur'an (MTQ) activity to form a young generation with insight and quality. This community service uses descriptive qualitative research with a case study approach. The subjects of community service are 85 participants. Data collection techniques in this community service are observation, interviews, and documentation. Data analysis uses triangulation. From the community service, it can be concluded that the increase in the actualization of the Qur'an through the MTQ activity in Sosokan Village, Ulu Rawas District, Muratara Regency went well during the activity. With three main activities that have been well organized, namely preparation activities, implementation activities, and evaluation activities. The implementation method used is increasing community knowledge by holding MTQ activities by combining lectures, training, and competitions to increase love and understanding of the Qur'an. The inhibiting factors are the lack of follow-up coaching programs after the MTQ is completed, the limited number of competent coaches, and the lack of supporting facilities. The supporting factors are the support of religious and community leaders, motivation and enthusiasm of participants in participating in MTQ activities, and routine coaching. Recommendations for further researchers are to provide broader insight into how MTQ is not only a competition event, but also a medium to build Islamic awareness and strengthen the values ​​of the Qur'an in everyday life.